2020
DOI: 10.3390/ijerph17030681
|View full text |Cite
|
Sign up to set email alerts
|

Adhering to the 2017 Dutch Physical Activity Guidelines: A Trend over Time 2001–2018

Abstract: Recently, new physical activity (PA) guidelines were adopted in the Netherlands consisting of two components: (1) addressing duration of moderate and vigorous PA, (2) bone and muscle strengthening activities. The aim of this study is to retrospectively assess the long-term trend in fulfilling the criteria of the new PA guidelines and to gain insight into which activities contribute to changes over time. Data were available for 2001–2018 of a nationally representative sample of approximately 7000 Dutch citizens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…The sociodemographic and lifestyle-related correlates of MSE observed in the present study are largely concordant with past research. Similar studies have shown inverse associations between meeting the MSE guideline for age, education/income levels and body mass index [34,36,43,44,47,62]. Moreover, studies have consistently shown that males and students are more likely to meet the MSE guidelines, compared to females and other occupational groups [34,38,43,44].…”
Section: Plos Onementioning
confidence: 75%
See 1 more Smart Citation
“…The sociodemographic and lifestyle-related correlates of MSE observed in the present study are largely concordant with past research. Similar studies have shown inverse associations between meeting the MSE guideline for age, education/income levels and body mass index [34,36,43,44,47,62]. Moreover, studies have consistently shown that males and students are more likely to meet the MSE guidelines, compared to females and other occupational groups [34,38,43,44].…”
Section: Plos Onementioning
confidence: 75%
“…Our finding on how MSE is patterned across Europe by degree of urbanisation is similar to our earlier Australian study [38], and suggest that efforts should be made to increase participation levels among those living outside high-density urban/metropolitan settings. Since the sociodemographic and lifestyle-related correlates of MSE are now becoming established [34,36,43,44,47,62], similar to research on the correlates of aerobic MVPA [63,64], we call for more research to assess the potential for a wider range of influences, such as social (behavioural modelling, social norms etc.) and physical environmental factors (access to equipment/facilities etc.).…”
Section: Plos Onementioning
confidence: 99%
“…5,7 Only in Dutch adults, the prevalence is reported considerably higher. 9 There are large methodological differences between the studies (ie, time frame, frequency/duration/volume/domain) in how PA levels were assessed that prevent direct comparison of the results. In measurement methodology, it remains challenging to assess muscle-strengthening PA in questionnaires, because many PA types can be considered both aerobic and muscle strengthening in nature.…”
Section: Discussionmentioning
confidence: 99%
“…13,18 Among older Dutch adults, increased time spent walking for leisure was seen as an explanation for the increased proportion reaching the aerobic and muscle-strengthening PA guidelines between 2001 and 2018. 9 In US adults, walking or walking in combination with some other PA type contributed most to adults reaching the aerobic PA guideline in 2000. 21 In our study, the odds ratios for walking in relation to reaching both components of the PA guidelines were strongest in older-aged women and weakest (not significant or even inversely associated) in working-aged women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation